The Grammaticalization Path of WH-Expletive Negation Constructions: From a Question Construction to an Adverbial Discourse Marker – The Case of Hebrew - Bardenstein, Ruti (Hebrew studies, 2025)
This paper focuses on wh-based exclamatives, both positive ones and negative ones, and claims that while the former evolve via the speaker's strong (usually negative) stance, the latter evolve via an argumentative stance implying exhaustivity, later turning into a discourse marking constructions of 'indifference', often defined in the literature as 'expletive negation'. These are standardly defined as cases where a sole negator seemingly does not modify the truth-value or truth-conditions of the proposition, or alternatively, the occurrence of a negative marker without apparent negative force. In this paper, I examine the linguistic evolution of wh-based negative exclamatives often defined as expletive negation (EN) and focus my analysis on Hebrew. The main claim is that positive wh-exclamatives and negative wh-expletives evolve via different rhetorical motivations, but in both cases it is the question's initial rhetorically-recruited function that motivates its semantic change (alongside grammatical and prosodic changes) and it is that function that also persists throughout their history. The paper offers constructionalization and grammaticalization processes of wh-EN exclamatives, focusing on the nature of the negator within those constructions.